The Relationship Between Organizational Silence and Organizational Citizenship Behavior Among Female Administrative Staff at King Abdulaziz University - Aljagthamy, Eman (مجلة العلوم الإدارية و الإقتصادية, 2025)
This study examines the relationship between organizational silence (OS) and organizational citizenship behavior (OCB) among female administrative employees at King Abdulaziz University, focusing on the impact of OS on five dimensions of OCB: altruism, courtesy, sportsmanship, conscientiousness, and civic virtue. Using a quantitative cross-sectional design with a sample of 176 employees, data were collected via a structured questionnaire adapted from validated scales. Correlation and regression analyses revealed significant negative relationships between OS and each OCB dimension, with OS also showing a strong predictive effect on the total OCB score. These findings highlight the detrimental role of OS in reducing employees’ engagement in discretionary behaviors critical to organizational success. The study underscores the need for policies that promote open communication, trust, and inclusivity to mitigate the effects of OS and foster a collaborative and proactive work environment.